Inadvertent doping through supplement use by athletes: Assessment and management of the risk in Australia - Baylis, A.; Cameron-Smith, D.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2001)
Many athletes report using a wide range of special sports foods and supplements. In the present study of 77 elite Australian swimmers, 99% of those surveyed reported the use of these special preparations, with 94% of swimmers reporting the use of non-food supplements. The most popular dietary supplements were vitamin or mineral supplements (used by 94% of the group), herbal preparations (61%), and creatine (31%). Eighty-seven percent of swimmers reported using a sports drink or other energy-providing sports food. In total, 207 different products were reported in this survey. Sports supplements, particularly supplements presented as pills or other non-food form, are poorly regulated in most countries, with little assurance of quality control. The risk of an inadvertent "positive doping test" through the use of sports supplements or sports foods is a small but real problem facing athletes who compete in events governed by anti-doping rules. The elite swimmers in this survey reported that information about the "doping safety" of supplements was important and should be funded by supplement manufacturers. Although it is challenging to provide such information, we suggest a model to provide an accredited testing program suitable for the Australian situation, with targeted athlete education about the "sports safety" of sports supplements and foods.